Mixed-methods findings from the Ngutulu Kagwero (agents of change) participatory comic pilot study on post-rape clinical care and sexual violence prevention with refugee youth in a humanitarian setting in Uganda - Logie, Carmen H.; Okumu, Moses; Loutet, Miranda; Berry, Isha; Lukone, Simon Odong; Kisubi, Nelson; Mwima, Simon; Kyambadde, Peter (Global public health, 2023)
There is a dearth of evidence-based post-rape clinical care interventions tailored for refugee adolescents and youth in low-income humanitarian settings. Comics, a low-cost, low-literacy and youth-friendly method, integrate visual images with text to spark emotion and share health-promoting information. We evaluated a participatory comic intervention to increase post-exposure prophylaxis (PEP) knowledge and acceptance, and prevent sexual and gender-based violence, in Bidi Bidi refugee settlement, Uganda. Following a formative qualitative phase, we conducted a pre-test post-test pilot study with refugee youth (aged 16-24 years) (n = 120). Surveys were conducted before (t0), after (t1), and two-months following (t2) workshops. Among participants (mean age: 19.7 years, standard deviation: 2.4; n = 60 men, n = 60 women), we found significant increases from t0 to t1, and from t0 to t2 in: (a) PEP knowledge and acceptance, (b) bystander efficacy, and (c) resilient coping. We also found significant decreases from t0 to t1, and from t0 to t2 in sexual violence stigma and depression. Qualitative feedback revealed knowledge and skills acquisition to engage with post-rape care and violence prevention, and increased empathy to support survivors. Survivor-informed participatory comic books are a promising approach to advance HIV prevention through increased PEP acceptance and reduced sexual violence stigma with refugee youth. Trial registration: ClinicalTrials.gov identifier: NCT04656522.